Recent progress in interfacial polymerization. (30th January 2017) - Song, Yongyang; Fan, Jun-Bing; Wang, Shutao
Abstract : Herein, recent progress in interfacial polymerization from the aspects of theory models, fabrication methods, and applications has been summarized. Abstract : Interfacial polymerization is one of the most important methods to fabricate polymer particles and membranes. As compared to bulk polymerization, interfacial polymerization is a type of step-growth polymerization that takes place at the interface of two immiscible phases, endowing the polymer materials with unique topological and chemical properties, such as anisotropic shapes, hollow structures or alternative surface chemistry. Herein, we summarize the recent progress in interfacial polymerization, generally based on the fabrication method and application field. First, two theory models of interfacial polymerization based on membrane and particles have been introduced. Second, five typical polymerization systems, i.e. liquid/monomer–solid (Lm –S), liquid/monomer–liquid (Lm –L), liquid/monomer–liquid/monomer (Lm –Lm ), liquid/monomer-in-liquid (Lm -in-L), and liquid/monomer-in-liquid/monomer (Lm -in-Lm ) systems, based on liquid–solid, liquid–liquid, and liquid-in-liquid emulsion interfaces, used in interfacial polymerization have been summarized. Then, three practical applications of synthetic materials, i.e. in electronic devices, separation, and cargo loading, prepared by interfacial polymerization have been shown. Finally, the current challenges and opportunities in interfacial polymerization have also been proposed and discussed.